Maks Kavčič 1909–1973: Ob predaji osebne zapuščine (University of Maribor Press, 2022)
Maks Kavčič 1909–1973: Uppon Submitting a Personal Estate. The manuscript material of the University Library of Maribor is the most valuable part of the library’s collection. It represents a collection of unique, sometimes private material, which, by being handed over to the library for safekeeping, has become part of the nation’s and universal cultural creativity, and thus cultural heritage. It has its origins in a personal author’s creation, which becomes public only when it is published. The material is varied in content, form and manner of creation. Most of the materials in the collection were donated (individually or as part of larger legacies), and a smaller part was acquired through purchases. Personal legacies testify to the nature of personal, literary and other contacts of creators, reveal the genesis of individual literary, scientific and artistic works and thus relevant biographical material. More than twenty personal legacies acquired in the last two years in the UKM Manuscript Collection were joined by a donation from the personal legacy of academic painter, set designer, restorer and pedagogue Professor Max Kavčič.